The use of 4.5% hypertonic saline challenge test in diagnosing asthma in children with chronic recurrent cough - Bambang Supriyatno; Dina Medina; Alan R Tumbelaka; Nastiti N Rahajoe (Indonesian Pediatric Society Publishing House, 2016)
Background The 4.5% hypertonic saline (HS) challenge test has several benefits compared to histamine challenge test as gold stan- dard. Saline is an inexpensive non-pharmacological substance which is relatively safe. Its mechanism in inducing bronchospasm resembles that of asthma. Moreover, it can easily be made in a modest medical laboratory. Objective To determine the ability of 4.5% HS challenge test com- pared to histamine challenge test in diagnosing asthma in children with chronic recurrent cough (CRC). Methods This study was a diagnostic test on children with CRC aged 6 to 14 years, conducted in outpatient clinic of Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta. All subjects underwent lung function tests. Subjects whose FEV 1 was <80% were diagnosed as asthmatic and underwent the 4.5% HS challenge test only. Those whose FEV 1 was 80% underwent the histamine chal- lenge test followed by the 4.5% HS challenge test one or two weeks later. Test results were expressed as positive or negative. Based on the results, we calculated the sensitivity, specificity, predictive val- ues, and likelihood ratios of the 4.5% HS challenge test. Results Forty-five subjects, consisting of 22 boys and 23 girls, were enrolled. The average age of subjects was 9 years old. Atopic history in the family or in subjects themselves was found in 80% of subjects. Eight subjects had FEV 1 of <80%. Forty-four subjects were diagnosed with asthma based on a baseline FEV 1 of <80% or a positive histamine provocation test. Thirty-seven subjects had a positive 4.5% HS challenge test; all had asthma. Sensitivity and specificity of the 4.5% HS challenge test were 84.1% and 100.0%, respectively; the positive and negative predictive values were 100.0% and 12.5%, respectively. The positive likelihood ratio was infinite and negative likelihood ratio was 0.16. Conclusion The 4.5% hypertonic saline challenge test can be used as an alternative bronchial provocation test in diagnosing asthma in children with CRC. Further study with larger sample size is needed for widespread usage.